Helicobacter pylori resistance to clarithromycin and quinolones in patients with dyspepsia in Tuzla Canton, Bosnia and Herzegovina - Ismar Hasukić; Nermin Salkić; Nijaz Tihić; Ervin Alibegović; Šefik Hasukić; Alan Jahić (Medicinski glasnik, 2023)
Aim: To evaluate Helicobacter pylori (H. pylori) resistance to clarithromycin and quinolones in patients with dyspepsia in Tuzla Canton, Bosnia and Herzegovina, a region with no data on clarithromycin or quinolones resistance. Methods: A prospective cross-sectional study was conducted at the Department of Gastroenterology and Hepatology at University Clinical Centre Tuzla between January 2021 and June 2022. The study included 99 patients who underwent esophagogastroduodenoscopy (EGDS) due to dyspepsia. In all patients biopsies were taken for rapid urease test (RUT) and histology findings, concomitantly with blood samples for IgG serology. All RUT positive patient samples were tested for clarithromycin and quinolones susceptibility with GenoType HelicoDr, a PCR method which detects point mutations in 23S rRNA and mutations in the gyrA gene. Results: Out of 99 dyspeptic patients, 67 (67.7%) were serologically positive to H. pylori, 46 (46.4.%) were RUT positive, and 19 (19.2 %) had a positive histology finding. Antibiotic (AB) resistance was tested in the total of 46/99 (46.4%) patients. Resistance to clarithromycin was detected in 28.26% (13/46), quinolones resistance in 36.96% (17/46) , and resistance to both AB was detected in 8.69% (4/46) tested biopsies. Conclusions: Due to high clarithromycin and quinolones resistance rates, we recommend the use of bismuth quadruple or non-bismuth concomitant quadruple therapy for H. pylori eradication in Tuzla Canton, Bosnia and Herzegovina.
Keywords: 23S rRNA; gyrA; HelicoDR; mutations; RUT; susceptibility